2009
DOI: 10.1061/(asce)0733-9399(2009)135:6(538)
|View full text |Cite
|
Sign up to set email alerts
|

Transient Modeling of Arbitrary Pipe Networks by a Laplace-Domain Admittance Matrix

Abstract: An alternative to modeling of the transient behavior of pipeline systems in the time-domain is to model these systems in the frequencydomain using Laplace transform techniques. Despite the ability of current methods to deal with many different hydraulic element types, a limitation with almost all frequency-domain methods for pipeline networks is that they are only able to deal with systems of a certain class of configuration, namely, networks not containing second order loops. This paper addresses this limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…(74)). Zecchin et al (2009) term the J H matrix a hydraulic admittance matrix, as it maps from pressure to flow. A more in-depth comparison of the element locations common to the formulations can be observed in (32) and (84).…”
Section: Comparison To Steady-state Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(74)). Zecchin et al (2009) term the J H matrix a hydraulic admittance matrix, as it maps from pressure to flow. A more in-depth comparison of the element locations common to the formulations can be observed in (32) and (84).…”
Section: Comparison To Steady-state Analysismentioning
confidence: 99%
“…Recently, Zecchin et al (2009) formulated a Laplace-domain network admittance matrix formulation of the fundamental network equations, which shares a similarity to the ĥ -formulation that is derived within this paper.…”
Section: Introductionmentioning
confidence: 97%
“…An alternative method for modelling systems comprised of pipes, junctions and reservoirs was proposed in Zecchin et al [2009] in which an admittance matrix expression relating the nodal pressures to the nodal outflows was derived from the basic fluid equations using graph theory concepts. The significance of this is twofold, (i) the network matrix was shown to have an intuitive and simple structure for which analogies with admittance matrices in electrical circuits was made apparent [Desoer and Kuh, 1969], and (ii) it showed that the entire network state was a function of the reduced variable set of nodal pressures and flows.…”
Section: Background Modelling the Transient Behaviour Of Pipe Networkmentioning
confidence: 99%
“…Firstly, as background for this work, the network admittance matrix for a simple node network is derived [Zecchin et al, 2009]. Based on this, a staged generalisation is presented.…”
Section: Network Formulationmentioning
confidence: 99%
See 1 more Smart Citation